2017
DOI: 10.1016/j.mri.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and neural basis of resting state functional connectivity: Evidence from non-human primates

Abstract: Functional MRI has evolved from simple observations of regional changes in MRI signals caused by cortical activity induced by a task or stimulus, to the development of task-free acquisitions of time series of images in a resting state. Such resting state signals contain low frequency fluctuations which may be correlated between voxels, and strongly correlated regions are deemed to reflect functional connectivity within synchronized circuits. Resting state functional connectivity (rsFC) measures have been widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…We used 8 Hz vibrotactile stimuli because it is a subtle and natural cutaneous stimulus that elicits robust touch sensation in humans and activates many cortical and subcortical brain regions, including S1 and S2 in the non-human primate 27 , 28 , 33 35 . We have previously demonstrated that many of the areas responding to such a stimulus are detectable as fMRI activations at ultra-high field (9.4 T) in the brains of squirrel monkeys under light anesthesia 30 , 31 and also show correlated signal variations in a resting state, reflecting their functional connectivity 36 , 37 . Extending our previous observations in squirrel monkeys, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used 8 Hz vibrotactile stimuli because it is a subtle and natural cutaneous stimulus that elicits robust touch sensation in humans and activates many cortical and subcortical brain regions, including S1 and S2 in the non-human primate 27 , 28 , 33 35 . We have previously demonstrated that many of the areas responding to such a stimulus are detectable as fMRI activations at ultra-high field (9.4 T) in the brains of squirrel monkeys under light anesthesia 30 , 31 and also show correlated signal variations in a resting state, reflecting their functional connectivity 36 , 37 . Extending our previous observations in squirrel monkeys, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While spinal electrophysiology has previously been performed in other animal models, the functional architecture and neural circuits of the central nervous system in NHPs share much greater similarities with those in humans. Previous reports have made use of NHPs to compare and understand the underlying biophysical basis of BOLD signals, but these were restricted to different cortices of the brain 37 . In this study, we have used NHPs to perform direct validation of MRI findings in the spinal cord using multichannel microelectrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic (buprenorphine) is for 3 days post-surgery. Detailed procedures have been described in our previous publication 12,5355 . All experimental procedures were in compliance with and approved by the Institutional Animal Care and Use Committee of Vanderbilt University, and followed the guidelines of the National Institute of Health Guide for the care and use of laboratory animals.…”
Section: Methodsmentioning
confidence: 99%